A methodology to investigate and optimise the crashworthiness response of foam-filled twelve right angles thin-walled structures under axial impact. (15th April 2023) - Liang, Rui; Liu, Xi; Hu, Yuanzhi; Jiang, Chengyue; Bastien, Christophe
Abstract: Multi-cell and foam-filled structures have shown outstanding crashworthiness capacities. As a result, foam-filled twelve right angles thin-walled structures (FTRATS), an integrator of them, can be excellent energy absorber candidates in the vehicle body structure. This paper presents a new methodology to investigate the crashworthiness potential of a series of novel FTRATS with different topological distributions. The base computer FTRATS model was correlated using existing experiments based on a single core thin-walled square tube filled with foam, then followed by a dynamic response evaluation of 32 FTRATS configurations, with the purpose of finding the lowest peak crushing force (PCF) and maximum displacement (Dmax), the highest specific energy absorption (SEA) and crash load efficiency (CLE). As the results were initially inconclusive, a complex proportional assessment (COPRAS) method was used to extract the configuration with the highest potential, suggesting that the five-cell FTRATS filled with foam at its periphery showed superior crashworthiness properties. This selection was followed by an optimization using adaptive multi-population genetic algorithm methods based on response surfaces methodology, kriging model and Optimal Latin hypercube design. The solution obtained generated a stable collapse, increased the CLE (63.94 %), lowered PCF (38.83%) and increased SEA (38.86%). This new and innovative process has shown that coupling COPRAS and optimisation lead to an unbiased and efficient method to study and optimize FTRATS structures.